Weed Control in Cole or Brassica Leafy Vegetables (Broc., Cabb., Caul., Collards, Mustard, Turnips, Kale) - William M. Stall (EDIS, 2009)
Revised! HS-189, a 5-page fact sheet by William M. Stall, describes effective weed management practices for cultivation of cole or Brassica leafy vegetables in Florida, and a table of chemical weed controls. Published by the UF Department of Horticultural Sciences, April 2009.